The new ranking method of the decision making units in DEA: with an approach to modifying the cross efficiency method. (2018) - Paryzad, Behzad; Najafi, Esmaeil; Kazemipoor, Hamed; Pour, Nasser Shahsavari
There is no doubt that organisations need an operation evaluation and measurement for having more efficiency and an optimal usage of their limited sources. One of the most practical methods for evaluating the operation is using the data envelopment analysis. Hence, data envelopment analysis (DEA) and ranking decision making units (DMU) are the most favourite subjects for the researchers. This method has modified on a different style on this article that has removed the existence of multiple optimal answers in the CCR (Chames-Cooper and Rhodes). In other words, the acquired ranks of the units are particular and have achieved with a special delicacy. In order to show the efficiencies of the method, some examples have presented that had achieved the more desirable and accurate ranking. The calculated results of performing this method have compared with the Anderson-Peterson method and its flexibility has studied according to the analysis of variance (ANOVA).